Autologous Pump‐Perfused Rat Hind Limb Preparation for Investigating Muscle Function and Metabolism In Vivo. (9th August 2013) - Peoples, Gregory E.; Hoy, Andrew J.; Henry, Renee; McLennan, Peter L.
Abstract Objective Oxygen delivery, underpinned by vascular tone, is the principle limiting factor in the study of skeletal muscle physiology, particularly during muscle contraction. The aim of this study was to develop an autologous perfused rat hind limb preparation for the study of skeletal muscle contractile function. Methods Adult Wistar rats were surgically prepared using a by‐pass system for pump‐controlled arterial blood flow to, and venous return from the hind limb during periods of quiescence and twitch contraction of the gastrocnemius‐plantaris‐soleus muscle bundle. Results During rest, hind limb perfusion pressure (102 ± 5 mmHg) was not different to systemic arterial pressure (99 ± 4 mmHg). Hind limb pressure was responsive to vasoconstrictors and vasodilators (±50 mmHg). The arterial PO2 (100 ± 3 mmHg), O2 saturation, and acid–base balance (pH: 7.42 ± 0.01) contributed to resting hind limb (a‐v)O2 difference (4.8 ± 0.5 mL/100 mL) and VO2 (0.31 ± 0.03 μmol/g/min wet weight). Repetitive isometric twitch tension (1 Hz, 0.05 ms, 10 minutes) was best maintained at a flow rate of 2 mL/min (VO2 increased fivefold during muscle contraction) and efficiency of oxygen use increased from 0.27 ± 0.08–0.52 ± 0.07 N/μmol/min. Conclusion The autologous rat hind limb provided resting vascular tone allowing maintenance of perfusion pressure at flows within the physiological range. Oxygen delivery supported repetitive twitch contractions and facilitated measurement of active metabolism.